Antibacterial Properties and Cytotoxicity of 100% Waste Derived Alkali Activated Materials: Slags and Stone Wool-Based Binders - Sgarlata, Caterina; Dal Poggetto, Giovanni; Piccolo, Federica; Catauro, Michelina; Traven, Katja; Češnovar, Mark; Nguyen, Hoang; Yliniemi, Juho; Barbieri, Luisa; Ducman, Vilma; Lancellotti, Isabella; Leonelli, Cristina (Frontiers in Materials, 2021)
In this study we compare the leaching behavior and the antibacterial and cytotoxic properties of 100% slag or stone wool derived alkali activated materials. The antibacterial activity was measured as the inhibiting capacity against two Gram-negative bacterial strains, Escherichia coli and Pseudomonas aeruginosa and one Gram-positive bacterial strain: Enterococcus faecalis. The cytotoxicity properties were tested on mouse embryonic fibroblast NIH-3T3 cell-line. It was proved that the high quality of the 3D aluminosilicate network of the consolidated materials obtained from powders of CaO or MgO-rich slags or stone wool, opportunely activated with NaO and/or Na-silicate, was capable to stabilize heavy metal cations. The concentrations of leachate heavy cations were lower than the European law limit when tested in water. The effect of additives in the composites, basal fibers or nanocellulose, did not reduced the chemical stability and slightly influenced the compressive strength. Weight loss in water increase of 20 % with basalt fibers addition, while it remained almost constant when nanocellulose was added. All the consolidated materials, cement-like in appearance, exhibited limited antibacterial properties (viability from 50 to 80% depending on the bacterial colony and the amount of sample) and absence of cytotoxicity, envisaging good acceptance from part of the final consumer and zero ecological impact. CaO-rich formulations can replace ordinary Portland cement (showing bacterial viability at 100%) with a certain capability for preventing the reproduction of the E. coli and S. aureus bacteria with health and environmental protection results.